Investigation of the potential of rice husk-based power plants and a pre-feasibility assessment of possible power plants in the An Giang province, Vietnam - Nguyen, Thu Trang (My University, 2014)
Biomass currently covers approximately 10% of the global energy supply. Rice husk is an agricultural biowaste having potential for power generation. In the An Giang Province, an important location for rice production in the Mekong Delta region in Vietnam, there is a high possibility for thermal power plants using rice husk. However, their feasibility in term of technology, socio-economy, and environmental benefits, needs to be investigated thoroughly. This study aims at (1) providing information of the current status of rice husk-related issues (e.g., logistics, market and price, current uses) in An Giang, (2) investigating the reasons why a rice husk-based power plant built in another location failed to generate electricity, and (3) producing a pre-feasibility assessment of two possible power plants owned by two selected rice mills which are likely to be constructed at their sites in the future. To answer these questions, a field trip was carried out in Vietnam for 7 weeks. 38 rice mills in An Gang were interviewed to obtain current status of rice husk at the local business level. Questionnaires and interviews with experts from the Institute of Energy in Vietnam, the Department of Environment and Natural Resources in An Giang, representative sof the Vietnam Electricity (the state-owned company, EVN), and the unsuccessful power plant fueled by rice husk in Can Tho Province were conducted. Site observations were also part of the investigation at the mills and the power plant. In addition, four rice mills were surveyed in detail, to prepare for a pre-feasibility study for two selected plants. The collected data was processed by using data analysis and pre-feasibility assessment methods. The results show that the current status of rice husk in An Giang reflects changes in several areas such as markets and policy in recent years in Vietnam. Rice husk has become a traded commodity producing profits to its rice mills and is used as fuel for drying systems or sold as raw material or in the form of briquettes, thus it is not wasted. Rice husk-based power plants may be more suitable at bigger scale rice mills. The investigation shows that low profit is the main cause of the failure of the unsuccessful power plant identified in Can Tho. The pre-feasibility assessment shows that most profitable solution for the studied rice huskbased power plants is that they are scaled to satisfy the energy demand of their own rice mill, and not to sell excess power to the grid. It is also discussed that combusion technology is most suitable to both studied power plants, with capacities of 670 kW and 580 kW, respectively. Carbon credits contribute only a minor share of the power plant's profitability.
Keywords: Energiteknik; Energy Engineering